Critical thinking the art of argument - Rainbolt, George W.; Dwyer, Sandra L. (Cengage Learning, 2015)
Shows students the relevance of critical-thinking skills by highlighting the advantages of basing one's decisions on a thoughtful understanding of arguments. The text emphasizes immediate application of critical-thinking skills to everyday life. Without sacrificing accuracy or detail, the authors have clearly presented the material with appropriate study tools and exercises that emphasize application rather than memorization.